MICRIBIOLOGICAL ASSESSMENT OF DRINKING WATER AND PERVASIVENESS OF WATER BORN DISEASES IN DUNGARPUR, RAJASTHAN - Ninama, Yogita (International Journal of Research -GRANTHAALAYAH, 2023)
INTRODUCTION: This study assessed E. coli counts in drinking water from different sources and illustrates the high prevalence of gastrointestinal diseases in Dungarpur districts of southern Rajasthan, India. METHODOLOGY: The microbiological parameters studied were pathogen detection, total coliform count and total viable count. Microbiological analysis of water samples were performed as described in Standard Methods for the Examination of Water and Wastewater (APHA - AWWA, 2005 and Chhabra, 2008). Total coliform count performed by the Most Probable Number (MPN) method, which is commonly used as an indicator of potability of water. Presence of the bacteria from Enterobacteriacae family was confirmed using IMViC test. The data of Indoor and Outdoor patients for such disease were collected. RESULT AND DISCUSSION: Seasonal fluctuation in coliform counts was found to be prominent and varied from over 200 MPN/ 100 ml in winter to more than 1600 (over the measurable limit) in rainy season in three water bodies. Escherichia coli counts ranged from 17 to 500 MPN/100 ml for all the sampled sites. E. coli and Total coliform were highest in rainy season. Results of IMViC test indicates that in rainy season except for Margia Dam all the water bodies were laden with all five categories of enteric bacteria namely E. coli, Shigella, Citrobacter and Klebsiella/ Enterobacter. The contamination is significantly higher during the wet season compared to dry season, due to WBD patients does exhibit a trend that in late summer and rainy month’s incidence of the disease symptoms intensifies. CONCLUSION: Dungarpur district was analyzed and same pattern of seasonal variation in microbial counts of water samples and similar hospital data trend was observed. So, somehow the microbial contamination of surface water and run-off reaches the ground-water table. Therefore, hospital data confirms that the source of drinking water plays a strong, positive and significant association with waterborne diseases.